Food Choices During Pregnancy Periods In Pulau Godang Kari : Pemilihan Jenis Makanan Selama Hamil di Desa Pulau Godang Kari - Vella Yovinna Tobing; Yati Afiyanti; Imami Nur Rachmawati (STIKes Hang Tuah Pekanbaru, 2019)
Cultural practice of nutritional consumption during pregnancy can affect the quality of maternal and fetal health. Mothers need sufficient nutrients to be able to adapt of pregnancy changes. The growth and development of the fetus is depends on the mother. Some cultural practices believe that some types of food have a bad impact on both the mother and the fetus, so that the food is prohibited to be consumed during the pregnancy period. The purpose of the study was to explore the types of prohibited foods during pregnancy in Pulau Godang Kari, Kuantan Singingi. This is an ethnographic research was conducted on 15 informants consisting of pregnant women, families, midwife and traditioanl birth attendance. Data collection used direct observation, focus group discussions and interviews that are analyzed by using content analysis. Prohibition of certain types of food based on the type of food that was believed that the properties are not good, so it was believed to have a bad effect on the mother and fetus. The implementation of cultural practices related to dietary restrictions is still being carried out, because of the belief that something unwanted will happen if you choose to consume these foods. Therefore, health workers must be able to provide culturally sensitive health services, so they can provide alternative food choices to fulfill nutritional needs during pregnancy period